Situação humanitária em Cabo Delgado: milhares de deslocados continuam sem assistência e apoio do Governo e das agências internacionais - Emídio Beula (Centro Para Democracia e Desenvolvimento (CDD), 2021)
Mais de 30.500 pessoas que abandonaram as suas casas devido aos ataques terroristas na vila de Palma em Março último continuam a enfrentar dificuldades de alimentação e de abrigo nos centros de acolhimento. A maioria está no centro de trânsito de Pemba e outros nos campos de deslocados de Metuge. A Matriz de Monitoria de Deslocamentos da Organização Internacional para as Migrações (OIM) continua a registar a chegada diária de deslocados que fogem da insegurança no norte de Cabo Delgado. As autoridades governamentais e as agências humanitárias interromperam, há mais de um mês, as operações de salvamento de pessoas que estão concentradas na vila de reassentamento de Quitunda, a menos de 30 quilómetros da vila de Palma. Devido à insegurança, as agências humanitárias não estão a prestar apoio a milhares de pessoas que estão em Quitunda, nas proximidades do acampamento de Afungi.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; displaced communities / comunidades deslocadas

Displacement Tracking Matrix - Mozambique Ett Report: No. 54/ 27 March - 26 April 2021 17:00h Emergency tracking tool (ett) - IOM - International Organisation for Migration (IOM, 2021)
Following the recent attacks in Palma Sede, DTM teams in Nangade, Mueda, Montepuez, and Pemba districts continue to register significant rise in IDP arrivals since 27 March. On 26 April 2021, an estimated number of 1,118 IDPs were registered in the four districts bringing the total number of IDPs to 27,913 people who have been displaced from Palma. IDPs continue to arrive in Nangade on foot and by bus from Nangade to Mueda, Montepuez, and Pemba.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; displaced communities / comunidades deslocadas

Displacement Tracking Matrix - Mozambique Ett Report: No. 54/ 27 March - 15 April 2021 17:00h Emergency tracking tool (ett) - IOM - International Organisation for Migration (ETT, 2021)
Following the recent attacks in Palma Sede, DTM teams in Nangade, Mueda, Montpuez, and Pemba districts continue to register significant rise in IDP arrivals since 27 March. On 15 April 2021, an estimated number of 1,260 IDPs were registered in the four districts bringing the total number of IDPs to 19,921 people who have been displaced from Palma. IDPs continue to arrive in Nangade on foot and by bus from Nangade to Mueda, Montepuez, and Pemba.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; displaced communities / comunidades deslocadas

Cabo Ligado Monthly: March 2021 - ACLED (ACLED, 2021)
In This Report: Analysis of the IS claim of the Palma attack in the context of the overall relationship between IS and the Cabo Delgado insurgency Discussion of growing tensions between displaced people, host communities, and aid organizations in districts with growing displaced populations Update on international involvement in the Cabo Delgado conflict and analysis of the role that South African companies Dyck Advisory Group and Paramount Group play in the conflict
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; displaced communities / comunidades deslocadas

UNHCR Mozambique IDP Response External Update 2-15 April.pdf - UNHCR (UNHCR - The UN Refugee Agency, 2021)
As of 15 April, over 20,0001 people from Palma are forcibly displaced, in the aftermath of Non-State Armed Group (NSAG) attacks on 24 March. They fled to the districts of Nangade, Mueda, Montepuez and Pemba by land, foot, air and sea. This is in addition to the nearly 700,000 already displaced in the provinces of Cabo Delgado, Nampula, Niassa, Sofala and Zambezia as a result of violence and insecurity in Cabo Delgado. UNHCR received reports that several families from Palma attempted to seek asylum in Tanzania due to the proximity to the border and were forcibly returned to Mozambique.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; accountability / responsabilização; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; displaced communities / comunidades deslocadas

Humanitarian Response Plan Mozambique (Humanitarian Programme Cycle 2021, 2020)
OCHA Humanitarian Response Plan for Northern Mozambique Conflict.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict / conflito; displaced communities / comunidades deslocadas

Cabo Delgado Crisis: Situation Report 1 - 14 April 2021 - Mozambique
English Situation Report on Mozambique about Camp Coordination and Camp Management, Health, Epidemic and more; published on 19 Apr 2021 by IOM
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; displaced communities / comunidades deslocadas